Geographic origins and patterns of radiation of Mertensia (Boraginaceae)1. Issue 1 (1st January 2014) - Nazaire, Mare; Wang, Xiao‐Quan; Hufford, Larry
Abstract : Premise of the study: Numerous molecular phylogenetic studies have used new biogeographic tools to explain species distributions. However, questions remain about origins, timing, direction of movement, and relationships between range expansion and diversification. We investigated geographic origins and temporal and spatial diversification of Mertensia, giving particular attention to divergence between Asian and North American lineages and radiation of western North American clades. Methods: Divergence time estimation and biogeographic analyses were based on phylogeny reconstruction inferred from nuclear ribosomal ITS and 12 plastid DNA sequence regions and a broad sampling of Mertensia, Boraginaceae, and core eudicots. Key results: Mertensia split from Asperugo in the late Oligocene to mid Miocene (26.83–12.22 million years ago [Ma]), followed by the first divergence in the crown group in the late Miocene (10.36–5.19 Ma). The ancestral area is inferred to have been Asia or a widespread distribution across Asia, Beringia, and circumboreal locales. Initial range expansion of North American Mertensia occurred in Beringia and the Pacific Northwest (7.70–4.22 Ma), followed by diversification of three clades (Pacific Northwest, southern Rocky Mountains, central Rocky Mountains). Conclusions: The crown divergence of extant Mertensia coincides with the onset of extreme cooling and fragmentation of a once extensive mixed mesophytic forest that was subsequently replaced by a boreal coniferous forest. Early diversification likely occurred when Beringia was connected and available for floristic exchange. The north–south orientation of the Rocky Mountain Range and Pleistocene glacial–interglacial cycles appear to have been important in the North American diversification of Mertensia .